Entrepreneurial intention among accounting students in UUM - Mohd Ariff, Arifatul Husna; Sharif, Zakiyah; Ahmad, Adura (Universiti Utara Malaysia, 2007)
The government strongly promotes entrepreneurship as a career choice among students.However, many students do not turn out to be an entrepreneur after their graduation. Students’ behavior and decision to involve in entrepreneurship can be explained by their intention. Therefore, this paper examines the relationships of attitude towards entrepreneurship, subjective norm and perceived behavior control on the students’ intention to be an entrepreneur based on Theory of Planned Behavior (TPB) model.A sample of 489 final year accounting students from University Utara Malaysia completed a questionnaire consisting of 19 items measuring attitude towards entrepreneurship, subjective norm, perceived behavior control, and intention to be an entrepreneur.The finding of the study shows that attitude, subjective norm, and perceived behavior control are significantly influence students’ intention to be an entrepreneur.This implies that TPB model is capable to predict students’ intention towards entrepreneurship, which at the end able to explain students’ decision and behavior to be an entrepreneur in the future.The implications to the university and policy maker are discussed further in this study.